Improvement of early detection of breast cancer through collaborative multi-country efforts: Observational clinical study - Aribal, Erkin; Mora, Patricia; Chaturvedi, Arvind K; Hertl, Kristijana; Davidović, Jasna; Salama, Dina H; Gershan, Vesna; Kadivec, Maksimilian; Odio, Clara; Popli, Manju; Kisembo, Harriet; Sabih, Zahida; et al. (Elsevier BV, 2019)
The aim of this paper is to present baseline imaging data and the improvement that was achieved by the participating centers after applying practice-specific interventions that were identified during the course of a multicentric multinational research coordinated project.
Keywords: Breast cancer, Screening, Mammography, BI-RADS, Quality assurance